Pesantren and Digital Literacy: Fiqh-Based Assessment of Islamic Teachers’ Competency in Strengthening Religious Moderation - Ma'arif, M Jauharul; Khoiriyah, Siti; Anwar, Saeful (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study highlights the urgency of developing the digital competence of Islamic Education (PAI) teachers through a fiqh-based approach oriented toward strengthening religious moderation, using a systematic literature review (SLR). The findings reveal that the integration of digital technologies in PAI learning faces several challenges, including limited training programs, the absence of valid evaluation instruments, low institutional readiness, and limited teacher motivation. The study emphasizes that digital competence is not merely a pedagogical necessity, but also an educational form of ijtihad that supports inclusive, adaptive, and non-extremist religious practices. Through the Technology Acceptance Model in Islamic Education, this study shows that religious perspectives play a dominant role in technology acceptance; therefore, digital literacy must be developed in alignment with fiqh principles such as maslahah and ijtihad as well as core values of religious moderation,particularly tawassuth (moderation), tasamuh (tolerance),and itidal (balanced judgment) in navigating digital information. Strengthening PAI teachers’ digital competence not only improves learning quality and student engagement, but also reinforces religious moderation within the Islamic education ecosystem in the digital era.